2015
DOI: 10.1128/mcb.00196-15
|View full text |Cite
|
Sign up to set email alerts
|

ARTD1 Suppresses Interleukin 6 Expression by Repressing MLL1-Dependent Histone H3 Trimethylation

Abstract: b ADP-ribosyltransferase diphtheria-toxin like 1/poly(ADP-ribose) polymerase 1 (ARTD1/PARP1) is a chromatin-associated protein in the nucleus and plays an important role in different cellular processes such as regulation of gene transcription. ARTD1 has been shown to coregulate the inflammatory response by modulating the activity of the transcription factor nuclear factor B (NF-B), the principal regulator of interleukin 6 (IL-6), an important inflammatory cytokine implicated in a variety of diseases such as ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 54 publications
(60 reference statements)
1
27
1
Order By: Relevance
“…Furthermore, the link between PARP activity and B cell function is supported by the observation that transcription factors known to contribute to the immune response, such as IL-2 and IFN-␥, most likely play a role in PARP-mediated gene regulation. PARP1 was recently demonstrated to modulate the expression of IL-6 in macrophages, supporting our observation of a role of PARP1 in the immune response (52). Although IL-6 regulation is independent of PARP1 activity in LCL cells, our data show that IL-2 and IFN-␥ may be dependent on PARP1 activity, reflecting different mechanisms of PARP1-mediated gene expression during the immune response.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the link between PARP activity and B cell function is supported by the observation that transcription factors known to contribute to the immune response, such as IL-2 and IFN-␥, most likely play a role in PARP-mediated gene regulation. PARP1 was recently demonstrated to modulate the expression of IL-6 in macrophages, supporting our observation of a role of PARP1 in the immune response (52). Although IL-6 regulation is independent of PARP1 activity in LCL cells, our data show that IL-2 and IFN-␥ may be dependent on PARP1 activity, reflecting different mechanisms of PARP1-mediated gene expression during the immune response.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies suggest that MLL1 expression and function can be regulated by NF-κB dependent signals(14, 25). As NF-κB signal transduction plays a central role in classical activation, we sought to determine if MLL1 expression and/or global H3K4me1/2/3 modifications were increased in macrophages in response to classical activation stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have identified an important role for NF-κB signal transduction in response to TNFα for the regulation of MLL1 expression and function in macrophages(14, 25). Our studies identified potent upregulation of Mll1 mRNA in response to LPS stimulation, which primarily signals through TLR4 and NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that ADP-ribosylation participates in inflammation (Bai and Virág 2012;Rosado et al 2013;Kunze and Hottiger 2019). PARP1 has been implicated in the mechanisms for responses (e.g., proinflammatory cytokine expression) of macrophages or macrophage-like cell lines to pathogen-associated molecular patterns (PAMPs), including lipopolysaccharide (LPS) (Hassa et al 2005;Liu et al 2012a;Yang et al 2014;Minotti et al 2015;Bohio et al 2019). Some responses involve the interplay between PARP1 and nuclear factor κB (NF-κB), a key B A Figure 1.…”
Section: Parp1 Induces Macrophage Activation and Inflammationmentioning
confidence: 99%
“…(P) Phosphate group; (ADPr) ADP-ribose; (Ac) acetyl modification; (yellow ciricle) ubiquitin. transcription factor in immunity and various other biological processes (Hassa and Hottiger 1999;Hassa et al 2005;Liu et al 2012a;Minotti et al 2015;Bohio et al 2019;Kunze and Hottiger 2019). Using PARP1-deficient mice Oliver et al (1999) provided evidence that PARP1 promotes NF-κB activation in macrophages in vivo.…”
Section: Parp1 Induces Macrophage Activation and Inflammationmentioning
confidence: 99%